Culture is everything : how to become a true culture warrior and lead your organization to victory - Veyera, Jeff Alan, 1971- (Quality Press, 2020)
"When it comes to winning in business, culture is EVERYTHING. Now there's a guide to aligning process, strategy, and culture to elevate your company's performance"--